Quality characterization of green mung bean cultivar Pag-asa 07-Mg 11 (Kintab) (Vigna radiata (L. Wilczek)) starch-based noodles and its corn (Zea mays) starch blend at various stage of noodle production - Mercado, Niño Sandro J.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Noodles -- Philippines; Starch -- Philippines; Corn -- Philippines; Mung bean -- Quality -- Philippines